First Report and Phylogenetic Analysis of Mitochondrial Genomes of Chrysomya villeneuvi and Sarcophaga genuforceps - Fengqin Yang; Jiao Xiao; Xiangyan Zhang; Yanjie Shang; Yadong Guo (Insects)
The mitochondrial genome, highly conserved across species, is crucial for species identification, phylogenetic analysis, and evolutionary research. Chrysomya villeneuvi and Sarcophaga genuforceps, two species with significant forensic value, have been understudied in terms of genetic data. In this study, the complete mitochondrial genomes of C. villeneuvi (15,623 bp) and S. genuforceps (15,729 bp) were sequenced and analyzed. All thirteen protein-coding genes (PCGs) exhibited Ka/Ks ratios below one, indicating purifying selection and supporting their utility as barcoding markers. Phylogenetic analysis and genetic distance calculations based on PCGs showed that C. villeneuvi is closely related to Chrysomya rufifacies and Chrysomya albiceps, and S. genuforceps aligns more closely with Sarcophaga kentejana and Sarcophaga schuetzei. This research is the first to provide mitochondrial genome data for C. villeneuvi and S. genuforceps, expanding the genetic resources available for Calliphoridae and Sarcophagidae and offering a foundation for further forensic and evolutionary studies.